Effects on rat T-helper cell proliferation by syngeneic epidermal cells exposed to IFN-gamma in vivo. - Skoglund, C (1989)
In several conditions in the skin, characterized by T-cell infiltration, keratinocytes are induced to synthesize and express class II transplantation antigens. The biological significance of this induced expression is still not understood. In this study, class II antigens were induced on rat ear keratinocytes by local intradermal injections into the ear of rat recombinant interferon-gamma (IFN-gamma). Epidermal cell suspensions prepared from these ears contained more than 50% class II-expressing cells, as judged by immunocytochemistry, compared with less than 5% in untreated epidermis. When comparing the capacity of these to different epidermal cell populations to stimulate a syngeneic PPD-specific T-helper cell line, it was found that IFN-gamma-exposed epidermal cells induced a lower T-cell response to PPD than did normal epidermal cells. This discrepancy could not be explained by either an infiltration of inflammatory cells into the epidermis of IFN-gamma-treated ears or by a difference in interleukin-1 production as determined in culture supernatants. The addition of indomethacin to cultures with IFN-gamma-exposed epidermal cells restored the T-cell response to PPD to that of normal epidermal cells, suggesting an inhibitory effect of prostaglandins. Our data indicate that epidermal cells exposed to IFN-gamma in vivo can suppress an antigen-specific T-cell proliferation.